2020
DOI: 10.1101/2020.09.02.273649
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dysregulation of hippocampal adult-born immature neurons disrupts a brain-wide network for spatial memory

Abstract: SummaryMounting evidence suggests that cognitive deficits associated with various neurological disorders may arise in part from a small population of dysregulated adult-born neurons in the dentate gyrus (DG). How these dysregulated adult-born neurons contribute to brain-wide network maladaptation and subsequent cognitive deficits remains unknown. Using an established mouse model with a small number of time-stamped dysregulated adult-born immature neurons and spatial memory deficits, we performed resting state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…We used an fMRI-compatible, spectrally resolved, fiber-photometry platform (Bao et al, 2020; Chao et al, 2022; Das et al, 2021; Meng et al, 2018; Oyarzabal et al, 2022; Zhang et al, 2022b, 2022a) with four recording fibers ( Figure 1A ) to measure neuronal GCAMP activity in the RSC, Cg, PrL, and AI from rats ( Supplementary Figure 1 ). GCaMP activity was combined with whole-brain fMRI recordings in anesthetized rodents to capture concurrent resting-state signals from both modalities ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used an fMRI-compatible, spectrally resolved, fiber-photometry platform (Bao et al, 2020; Chao et al, 2022; Das et al, 2021; Meng et al, 2018; Oyarzabal et al, 2022; Zhang et al, 2022b, 2022a) with four recording fibers ( Figure 1A ) to measure neuronal GCAMP activity in the RSC, Cg, PrL, and AI from rats ( Supplementary Figure 1 ). GCaMP activity was combined with whole-brain fMRI recordings in anesthetized rodents to capture concurrent resting-state signals from both modalities ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…A MRI-compatible, four-channel, spectrally resolved, fiber-photometry platform was used (Bao et al, 2020; Chao et al, 2022; Das et al, 2021; Meng et al, 2018; Oyarzabal et al, 2022; Zhang et al, 2022b, 2022a). We used interleaved 488 nm (OBIS Galaxy Laser 1236444, Coherent, Santa Clara, CA) and 405 nm (OBIS Galaxy Laser 1236439, Coherent, Santa Clara, CA) diode lasers for GCaMP signal excitation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dentate gyrus is an important region for processing spatial information, and newborn neurons are integrated into this network (Clelland et al, 2009; Kee et al, 2007; Toda et al, 2019). A recent study has shown that just a few hundred dysregulated adult-born immature neurons can cause aberrant activity in CA3 and CA1 hippocampus, leading to brain-wide disruptions in neural connectivity that impair spatial memory (Bao et al, 2020). Consistent with this finding, in this study we observed extensive accumulation of DCX+/Neurod1+ immature cells in the GCL of Ppm1k cKO mice that could contribute to disturbances in spatial working memory.…”
Section: Discussionmentioning
confidence: 99%